AVALIAÇÃO DA APRENDIZAGEM: CONCEPÇÕES E PRÁTICAS DE FORMADORES DE PROFESSORES - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2007)
This research aims to the avaliation conceptions and practices related to formators of professors in education courses. The focuses are: a) identifying, describing and analysing avaliative conceptions and practives of professors's formators; b) focusing on formative critical avaliation as a possible tool at superior teaching; c) putting discussions about avaliative practices up used in teaching courses and their outcomes of formation for future teachers. Uneasiness justify this research since there is a great number of notpassed and school-quitted students in basic education, whereby they come with social problems, as a loss of budged reserved for education. Lacking of coherence from what is said to practices in teaching courses and traditional avaliative practices are held as natural rituals. This work makes up for history of education, avaliation and teachers' work; analysing traditional avaliation along with critical one under discrete interests from capitalist context which drags pedagogical actions. Also, it seeks understanding the process of formation of teacher in education courses at space. Enhancing the formative critical avaliation, it is appraised for reflexive and approached to social reconstruction. The methodological standpoint is qualitative, stressing into magistery courses at the universe, due to the lowest and highest approval in 2004. Database procedures were done by non-directive and semi-directive advice in questionaires, along with collective interview, and answered by last-year students and mentors, to identify avaliative conceptions and practice from those courses. Analitical results generate the following cathegories: dominance of avaliative tools assented to traditional; professors' preference for tools the less time or easy to avaliate, even habitual; avaliation as the learnig process end, and not part of; lack of fews avaliative practices to the development of student's authonomy in his construtive learning process; avaliation of mentor's work through the avaliation of students; avaliation as mere record or students's outcomes certified document. The results of this research point to the need of continuously formation work of formators, which quiries their avaliative and learning representation, and being conscious of mentors practice and propounding alternatives of changes about avaliative learning strategies of superior education.
Keywords: avaliação; ensino-aprendizagem; ensino superior; licenciaturas; formação de professores; avaliation; teaching and learning; superior education; education courses; formation of professors; CNPQ::CIENCIAS HUMANAS::EDUCACAO